Payment system settlement and bank incentives - Charles M. Kahn; William Roberds (Federal Reserve Bank of Atlanta, 1996)
In this paper we consider the relative merits of net versus gross settlement of interbank payments. Net settlement economizes on the costs of holding non-interest-bearing reserves but increases moral hazard problems. The "put option" value of default under net settlement can also distort banks' investment incentives. ; Absent these distortions, net settlement dominates gross, although the optimal net settlement scheme may involve a positive probability of default. Net settlement becomes more attractive relative to gross settlement if bank assets have to be liquidated at less than book value.
Keywords: 330; Financial institutions; Financial services industry; Payment systems